The Feminine Beast: Anti-moral Morality in Early 20th-Century Literature (Konturen, 2014)
Texts of the early Twentieth Century link animalism, gender struggles, and issues of identity in their stark critique of bourgeois gender ideology. This essay places selected texts by Bertolt Brecht and Frank Wedekind in the center of this debate as they elaborate on Friedrich Nietzsche’s critique of the Western nature/culture divide and his animal imagery. For Brecht, corruption of bourgeois value systems, including gender concepts, undermines any possibility for an authentic lifestyle, whereas Wedekind ¬– a generation earlier – explores the corruptibility of authenticity itself.